Spiritual senses as a resource - Haapalainen Anna (Finnish Society for the Study of Religion, 2025)
This article discusses knowledge gained through experiencing the presence of God through the ‘spiritual senses’ as a resource in an Evangelical Lutheran parish. Believers’ being-in-touch experiences with the divine produce a special kind of knowledge that can be shared and passed on in the parish. This ‘spiritual asset’ plays an important part in parochial activities. This development can be explained by the rise of experience-based religiosity and charismatic Christianity, a global Christian trend which is also affecting the mainline churches.